(untitled) (Research, Society and Development, 2023)
This article aimed to reflect on interdisciplinarity in the academic environment, making references to the converging and divergent conceptions of the term, given the complexity of understanding, but also the possibility to carry out a differentiated work in the classroom from the theories proposed in this fundamental part of this research. In this sense, it is understood that through this alternative work, the teacher will be able to encourage students to conceive knowledge from different angles from those proposed only in a single scientific knowledge. To understand the proposed theme, a qualitative methodology was used to describe theories that approached interdisciplinarity in the academic environment and its importance for the development of student learning in the school environment. Therefore, analyzes of books, internet research and scientific articles were carried out to really understand how school work has been carried out through interdisciplinarity. In this view, it was observed that interdisciplinarity has contributed to the development of students in the school environment, expanding their learning repertoire, and thus, enabling new knowledge. In addition, the teacher is fundamental so that this teaching practice can be successfully carried out in the classroom, since he is the mediator of knowledge, of conflicts, he is, therefore, the one who works with the pedagogical and scientific part in the classroom. of class. However, it should be remembered that the difficulties in understanding the interdisciplinary process will exist, however, from a work that glimpses the autonomy of students in the classroom and encourages them to deepen their knowledge about the proposed theme, it will not be difficult to understanding, which will contribute to the learning of new knowledge. Thus, the elaboration of this article does not exhaust the dissected theme, but will contribute to the collection that already exists on the proposed subject, which will allow a review of the proposed design.